On Roald Amundsen’s scientific achievements - Blix, Arnoldus Schytte (Polar Research, 2016)
This paper describes the significant direct and indirect contributions to science made by the Norwegian polar explorer Roald Amundsen in the period 1897–1924. It documents that his expeditions through the North-west Passage (1903–06) with Gjøa, to the South Pole (1910–12) with Fram and through the North-east Passage (1918–1920) and the Chukchi and East Siberian seas (1921–25) with Maud yielded vast amounts of published scientific material on meteorology, terrestrial magnetism, geology, palaeontology, oceanography, ethnography, zoology and botany, which, though celebrated at the time, have since received scant recognition in more recent assessments of Amundsen’s achievements. Keywords: Fridtjof Nansen; polar exploration; South Pole; North-west Passage; North-east Passage; H.U. Sverdrup.
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; ekspedisjoner; forskning; geologi; meteorologi; oseanografi

Changing the Look on Seals from Pole to Pole with Satellite Technology - Blix, Arnoldus Schytte; Folkow, Lars P; Nordøy, Erling S (Adaptation and Evolution in Marine Environments, Volume 2: The Impacts of Global Change on Biodiversity, 2013)
Keywords: Sørishavet; marin biologi; observasjoner; pattedyr; seler; sjøpattedyr

Distribution, density and abundance of Antarctic ice seals off Queen Maud Land and the eastern Weddell Sea - Gurarie, Eliezer; Bengtson, John L; Bester, Marthán N; Blix, Arnoldus Schytte; Cameron, Michael; Bornemann, Horst; Nordøy, Erling S; Plötz, Joachim; Steinhage, Daniel; Boveng, Peter (Polar Biology, 2017)
Keywords: Sørishavet; Weddellhavet; marin biologi; observasjoner; pattedyr; seler; sjøpattedyr; zoologi